MENGGALI KETERKAITAN BUDAYA ORGANISASI DENGAN TINGKAT STRES DAN KELELAHAN PERAWAT DI RUMAH SAKIT: SYSTEMATIC REVIEW - Gorean, Grace Irma; Novieastari, Enie; Wildani, Andi Amalia; Gayatri, Dewi (Media Penelitian dan Pengembangan Kesehatan, 2025)
Organizational culture is summary of shared values, beliefs, or perceptions held by employees in  organization or organizational unit and can influence staff attitudes and behaviors. This has impact the quality of life of nurses, including health, emotional exhaustion, job satisfaction, work stress. . The purpose this study to explore relationship between organizational culture and levels of stress and burnout among nurses in hospitals, provide more objective and comprehensive description of the existing evidence, identify knowledge gaps, and provide recommendations based on consistent findings.This research method is  detailed analysis using the PRISMA flow diagram, Literature search in several databases, namely Proquest, Science Direct, Taylor & Francis Online, PubMed, Sage, Whiley and Scopus which are published. Article quality assessment using the JBI Joanna Briggs Institute Critical Appraisal Checklist for Analytical Cross Sectional Studies. Eleven articles were identified and analyzed that met the inclusion criteria; articles have abstract and full text, search type in the database with journal articles, published in English, articles published in the last 10 years 2014 - 2024, articles discussing organizational culture; positive organizational culture consisting of; open and transparent communication, strong social support, good teamwork, trust and appreciation for nurses, safe and comfortable work environment, articles discussing stress levels and burnout of nurses in hospitals. Exclusion criteria: articles cannot be accessed as full text, books, are literature reviews, theses, books. The results of the synthesis show a positive organizational culture is less likely to indicate stress levels and burnout in nurses.